You sexy thing - Rambo, Cat (Tor/Tom Doherty Associates, 2021)
"Farscape meets The Great British Bake Off in this fantastic space opera You Sexy Thing from former SFWA President, Cat Rambo. Just when they thought they were out... TwiceFar station is at the edge of the known universe, and that's just how Niko Larson, former Admiral in the Grand Military of the Hive Mind, likes it. Retired and finally free of the continual war of conquest, Niko and the remnants of her former unit are content to spend the rest of their days working at the restaurant they built together, The Last Chance. But, some wars can't ever be escaped, and unlike the Hive Mind, some enemies aren't content to let old soldiers go. Niko and her crew are forced onto a sentient ship convinced that it is being stolen and must survive the machinations of a sadistic pirate king if they even hope to keep the dream of The Last Chance alive"--